THE INFLUENCE OF TURKISH TV SERIES ON THE YOUTH THROUGH THE PRISM OF MODERN CULTURE (Journal of Contemporary Philology, 2023)
Turkish television series have achieved a significant transformation and transcended the geographical boundaries of the Republic of Türkiye. This cultural phenomenon extended its reach to the Republic of North Macedonia and achieved immense popularity. Tо explain the features of the phenomenon, this paper analyses the attitudes of high school students via a survey, as well as identifies the potential benefits and challenges arising from such cultural exchange. It also aims to analyse the multifaceted dimensions of the influence of Turkish television series, their popularity, and their influence in language acquisition.The results provide insights into the role played by Turkish television series in shaping the personality profile and attitude towards contemporary culture among young people.
Keywords: contemporary culture; television series; youth; personality profile; language